THE IMPACT OF FOOD MARKETING ON THE LIVES OF CHILDREN AND ADOLESCENTS (CIPEEX, 2022)
FOOD MARKETING DIRECTLY INFLUENCES THE LIVES OF CHILDREN AND ADOLESCENTS, RESULTING IN THE HIGH CONSUMPTION OF UNHEALTHY FOODS IN THIS AGE GROUP, WHICH CAN BE DEMONSTRATED BY THE NUMBERS: AMONG THE 1 BILLION OBESE PEOPLE WORLDWIDE, 340 MILLION ARE ADOLESCENTS AND 39 MILLION ARE CHILDREN. (WHO, 2022). FIRST OF ALL, THIS MINI INTEGRATIVE REVIEW AIMED TO ANALYZE THE EFFECTS OF FOOD ADVERTISING ON CHILDREN€™S HABITS. FOR THIS, A DATA SEARCH WAS USED AS A METHODOLOGY THROUGH THE US NATIONAL LIBRARY OF MEDICINE (PUBMED), BETWEEN THE YEARS 2019 AND 2022, BASED ON HEALTH SCIENCES DESCRIPTORS (DECS): €ŒCHILD€; €ŒADOLESCENT€; €ŒDIET€; €ŒHEALTHY€; €ŒEATING€; €ŒMARKETING€; €ŒNUTRIONAL REQUIREMENTS€; €ŒSOCIAL MEDIA€; €ŒFOOD INDUSTRY€; €ŒNUTRITIVE VALUE€; €ŒTELEVISION€; €ŒDIETARY SUGARS€; USING THE BOOLEAN AND BETWEEN THEM. IN VIEW OF THIS, A SIGNIFICANT INCREASE IN THE CONSUMPTION OF LOW-NUTRIENT DIETS WAS OBSERVED IN CHILDREN WHO SAW INFLUENCERS WHIT UNHEALTHY SNACKS. THERE WAS AN ABUNDANCE OF ADVERTISING ABOUT UNHEALTHY FOODS EVERY DAY TO CHILDREN, WHICH HAD A NEGATIVE IMPACT, AS THE OBESITY AND CAVITIES, BECAUSE OF INCREASE IN HIGH-CALORIED PRODUCTS IN THE DIET OF MINORS. TO CONCLUDE, IT IS FUNDAMENTAL TO MAKE THE QUANTITATIVE EXIBITION OF NUTRITIOUS FOOD AND HIGH-CALORIE PRODUCTS EGALITARIAN, ADDED TO THE RESTRICTION OF BAD TECNICS IN ADVERTISEMENTS, WITH THE AIM THAH THE TARGET PUBLIC IS SEEN NOT AS PROFIT, BUT AS INDIVDUALS IN TRAINING.